1998
DOI: 10.1086/514713
|View full text |Cite
|
Sign up to set email alerts
|

Limulus Amebocyte Lysate Assay for Detection of Endotoxin in Patients with Sepsis Syndrome

Abstract: Clinical predictions alone are insufficiently accurate to identify patients with specific types of bloodstream infection; laboratory assays might improve such predictions. Therefore, we performed a prospective cohort study of 356 episodes of sepsis syndrome and did Limulus amebocyte lysate (LAL) assays for endotoxin. The main outcome measures were bacteremia and infection due to gram-negative organisms; other types of infection were secondary outcomes. Assays were defined as positive if the result was > or = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 42 publications
4
48
0
Order By: Relevance
“…Even though the LAL assay has been used in most studies dealing with endotoxemia measurement, it has repeatedly been reported to be negative in some patients with sepsis ( 32,33 ), and not to be clinically useful for detecting Gram-negative infections or predicting patient outcomes ( 16,34,35 ). Surprisingly, earlier studies reported that LAL positivity was observed in only 20% of patients presenting …”
Section: Discussionmentioning
confidence: 99%
“…Even though the LAL assay has been used in most studies dealing with endotoxemia measurement, it has repeatedly been reported to be negative in some patients with sepsis ( 32,33 ), and not to be clinically useful for detecting Gram-negative infections or predicting patient outcomes ( 16,34,35 ). Surprisingly, earlier studies reported that LAL positivity was observed in only 20% of patients presenting …”
Section: Discussionmentioning
confidence: 99%
“…The remaining very ill patients had serial blood and other relevant cultures performed, but no causative agent was found. However, it is possible that some of these patients had endotoxemia as the underlying cause of disease [21].…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Endotoxemia has been correlated with prognosis in dogs with pyometra, 24 and there was a trend for endotoxin to be correlated with outcome in CPV, 4 but endotoxin in circulation may be transient or circulating inhibitors may interfere with measurement. 25,26 Endotoxin can be difficult to measure, 26 and the method used for this study was different from that used previously.…”
Section: Discussionmentioning
confidence: 99%